A comparative analysis of housing policies of Namibia and South Africa - Mathe, Audrin (Graduate School of Development Policy and Practice, 2019)
Both Namibia and South Africa have had mixed success in their housing policies since the advent of democracy in both countries in the 1990s. This paper proceeds from the hypothesis that each country can learn useful lessons from each other in respect of housing policy. The primary purpose of this research was to describe and systematically compare the housing policies of Namibia and South Africa. The historical backgrounds of the countries, existing policies and the manner in which the policies are implemented were investigated. The research examined the housing policies of Namibia and South Africa in terms of their similarities and differences and to consider the impact and implications. Namibia and South Africa vary in their expenditure commitments to provide affordable homes. Their housing policy strategies also differ. Differences reflect different levels of prosperity and differences in governance and institutional arrangements. The study concluded that the policies of Namibia and South Africa are, in the main, similar in that both Namibia and South Africa have enacted legislation that govern matters related to housing – either as housing relates to financing and affordability or as a function of ownership. South Africa stands out, however, in that the right to adequate housing is a prescript of the constitution. In both the investigated countries, there is evidence that their policies are committed to a housing process built on the foundations of people’s participation and partnerships. But there are also differences with regard to implementation. In this study, it is brought to bear on both countries that the provision of housing was not all that successful. But good policies are a good start to a successful outcome of a process.